Competences of airport services in maintenance of the movement area - Urban, Krzysztof (Wydawnictwo Politechniki Łódzkiej, 2012)
One of the fundamental activities performed at an airport is its maintenance in the condition which enables safe and efficient air operations. The conditions specified in Annex 14 to the Convention on international civil aviation obligate the member states to take any essential measures to remove all contamination from the movement area as quickly and efficiently as possible in order to ensure a proper adhesion coefficient (friction coefficient) and low rolling resistance. Furthermore, Annex 14 contains a demand for maintaining the surfaces clean and removing stones and other objects which may damage the construction of wings or engines or reduce the efficiency of other airplane subassemblies. It should be emphasized here that the main and the most important responsibility of airport services is to remove all contamination and waste which could have any adverse effect on air operations from the apron and the movement area. Therefore, research is constantly being conducted aiming at the optimization of economic and use conditions as well as the efficiency of mechanic and chemical methods of removing contaminations from the apron and the movement area. In addition, it is also necessary to measure the friction coefficient and, what follows, to develop best possible methods of such measures.The efficiency of airport services in the maintenance of the movement area depends, to a great extent, on competences of these services and their experience, which make it possible to perform the assigned tasks and responsibilities properly. A high level of competences of airport services has an influence on making good and correct decisions, what is sometimes critical for safety in the maintenance of the movement area
Keywords: globalization-management; Business management-innovation; globalizacja; zarządzanie; innowacje